Arranging Regulatory Policies to Support Economic Growth, Investment, Industrial Revolution 4.0, Society 5.0, and the Global Economy with Omnibus Law - Simanjuntak, Ronald TA; Panjaitan, Marojahan JS; Saragih, Bintan R. (Global Legal Review, 2024)
Arranging regulatory policies to support economic growth, investment, the Industrial Revolution 4.0, Society 5.0, and the global economy using the omnibus law turned out to be problematic. Among the people, there are pros and cons because it is not following the Indonesian legal system, which follows the "civil law" tradition. It is necessary to research the pros and cons of this research. The purpose of this research is to analyze the effectiveness of the omnibus law policy in managing regulations to support economic growth, investment, Industrial Revolution 4.0, Society 5.0, and the global economy. The research method used is normative legal research with a literature study approach. This study concludes that implementing the omnibus law policy in managing regulations to support economic growth, investment, the Industrial Revolution 4.0, Society 5.0, and the global economy is very effective and efficient because the formation is cheaper, faster, and avoids various political conflicts. Law policies formed using the omnibus law method are part of the national legal system. Therefore, the omnibus law policy in managing regulations must refer to the provisions and principles regulated in Law Number 12 of 2011 on the Establishment of Legislation as amended by Law Number 15 of 2019 and Law Number 13 of 2022 and its implementing regulations, Presidential Regulation Number 87 of 2014 and Number 76 of 2021, as well as general and universal principles, the principles and concepts of customary law or, in some instances, the principles and concepts of Islamic law. Everything is elaborated in a direction based on the omnibus law method so that the law developed based on the omnibus law method can create happiness for the Indonesian people, as mandated in the fourth paragraph of the opening of the 1945 Constitution.